"Les Levine copies everyone" - Bourdon, David (Toronto : The Isaacs Gallery, 1970)
The contents include photocopied documentation of press releases, articles, and other documentation, including from the 1970 exhibition which this was published in conjunction with. It includes an article entitled “Conceptual and Decorative Elements in the Graphic Work of Les Levine” by David Bourdon, a checklist of works in the show, a bibliography and biography, reproductions of works, etc.
"Les Levine copies everyone", at The Isaacs Gallery, Toronto, October 20 to November 9, 1970
Engels
boek
Keywords: Levine, Les